Electrochemical vicinal aminotrifluoromethylation of alkenes: high regioselective acquisition of β-trifluoromethylamines 1. Issue 20 (1st May 2019) - Huang, Yubing; Hong, Huanliang; Zou, Zirong; Liao, Chunshu; Lu, Jingjun; Qin, Yongwei; Li, Yibiao; Chen, Lu
Abstract : A high-regioselective electrochemical aminotrifluoromethylation of alkenes leading to β-trifluoromethylamines using CF3 SO2 Na as a trifluoromethyl precursor and acetonitrile as an N -nucleophile was achieved. Abstract : A novel vicinal aminotrifluoromethylation of alkenes using CF3 SO2 Na as a trifluoromethyl precursor and acetonitrile as an N -nucleophile has been achieved by an electrooxidative strategy. The present electrochemical protocol achieves efficient and highly regioselective difunctionalization of CC bonds under metal-free and external oxidant-free electrolysis conditions, leading to a series of β-trifluoromethylamine compounds with good to excellent yields. It is confirmed that the reaction involves free radical processes since CF3 radicals are trapped by scavengers and the β-trifluoromethylated radical is trapped by BHT, and the deuterium-labeling experiments prove that the oxygen in the product comes from water.